2002
DOI: 10.2741/pessah
|View full text |Cite
|
Sign up to set email alerts
|

Redox sensing properties of the Ryanodine receptor complex

Abstract: The release mechanism regulating SR Ca2+ homeostasis is significantly more sensitive than the uptake mechanisms. The exquisite sensitivity exhibited by ryanodine-sensitive Ca2+ channel complexes (i.e., ryanodine receptors, RyRs) to functional perturbation by chemically diverse sulfhydryl-modifying compounds can include phases of activation and inhibition that are dependent on the concentration of the reagent used, the length of exposure, and the nature of the chemical reaction the reagent undertakes with sulfh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…As discussed below, this increase is possibly the result of RyR redox modifications, which are known to modify RyR activity (Donoso et al, 2000;Eu et al, 2000;Xia et al, 2000;Pessah et al, 2002;Aracena et al, 2003). In particular, oxidation or alkylation of critical SH residues with dithiodipyridine or thimerosal, respectively, causes single RyR channel from rat brain cortex to display higher degrees of activation in response to Ca 2ϩ (Marengo et al, 1998;Bull et al, 2003Bull et al, , 2007.…”
Section: Brain Tissue Redox State During Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed below, this increase is possibly the result of RyR redox modifications, which are known to modify RyR activity (Donoso et al, 2000;Eu et al, 2000;Xia et al, 2000;Pessah et al, 2002;Aracena et al, 2003). In particular, oxidation or alkylation of critical SH residues with dithiodipyridine or thimerosal, respectively, causes single RyR channel from rat brain cortex to display higher degrees of activation in response to Ca 2ϩ (Marengo et al, 1998;Bull et al, 2003Bull et al, , 2007.…”
Section: Brain Tissue Redox State During Ischemiamentioning
confidence: 99%
“…Therefore, RyR channels could amplify by CICR the cytoplasmic [Ca 2ϩ ] increase caused by Ca 2ϩ entry during cerebral ischemia. The redox state of highly reactive cysteine residues regulates RyR channel activation, enabling these channels to act as cellular redox sensors (Eu et al, 2000;Xia et al, 2000;Pessah et al, 2002). In particular, RyR redox state determines the three types of response (low, moderate, or high) to cytoplasmic [Ca 2ϩ ] increases of single RyR channels from rat brain cortex ER (Marengo et al, 1996(Marengo et al, , 1998Bull et al, 2003Bull et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperphosphorylation is thought to occur after chronic β-adrenergic stimulation, such as during congestive heart failure. Furthermore, redox modifications of the RyRs tend to increase their Ca 2+ sensitivity in various conditions of cellular stress, when excessive amounts of reactive oxygen species (ROS) are produced (Pessah et al 2002;Sanchez et al 2005;Jung et al 2008). If more than one of these sensitizing conditions occurs simultaneously, either alone or together with elevated SR Ca 2+ load, the CICR mechanism may become unstable.…”
Section: Possible Implications Of Reduced S100a1 Levelsmentioning
confidence: 99%
“…Multiple cellular componentsincluding ATP, H C , Ca 2C and Mg 2C -and specific proteins, including kinases and phosphatases, as well as endogenous oxidative/nitrosative species, regulate RyR channels (Fill & Copello 2002). In particular, many studies have reported modifications of RyR cysteines by non-physiological redox compounds (for reviews, see Hamilton & Reid 2000;Pessah et al 2002;Hidalgo et al 2002). These studies have contributed to the current understanding of how these cysteine modifications change RyR function and affect Ca 2C release; they have also promoted active research into how redox compounds of physiological significance affect RyR activity.…”
Section: Introductionmentioning
confidence: 99%
“…The redox sensitivity of skeletal RyR1 is due to the presence of highly reactive cysteine residues in the RyR1 molecule, which have a pK value of 7.4 (Liu et al 1994;Pessah et al 2002) and allow RyR1 redox modification at physiological pH. Additionally, RyR1 exhibit a well-defined redox potential (Feng et al 2000;Xia et al 2000); through this property they may be susceptible to changes in cellular redox potential.…”
Section: Introductionmentioning
confidence: 99%